A Review on High‐Strength Titanium Alloys: Microstructure, Strengthening, and Properties. Issue 8 (11th June 2019) - Kang, LiMei; Yang, Chao
Abstract : The authors review the recent advances in the development of high‐strength titanium alloys. First, they summarize conventional strengthening approaches and their mechanisms, thecorresponding microstructures, and the optimized mechanical properties. Subsequently, various strengthening strategies for high‐strength titanium alloys are discussed. Finally, examples of the successful development of high‐strength titanium alloys based on amorphous crystallization via solid and semi‐solid sintering are presented. The review of the interrelation between the microstructure, the strengthening, and the properties may provide significant insight into achieving novel high‐strength titanium alloys. Abstract : Development of bimodal/multimodal microstructure has attracted extensive attention in the balance of high strength and ductility of titanium alloys. This review covers the development strategies of ultrahigh strength titanium alloys consisting of nanoscale and microscale grains. Specially, a novel semi‐solid sintering technique for preparing bimodal structured titanium alloys composed of nanostructured eutectic matrix and micron‐sized precipitated phases has been proposed.